Women’s empowerment in agriculture: Lessons from qualitative research - Meinzen-Dick, Ruth S.; Rubin, Deborah; Elias, Marlène; Mulema, Annet A.; Myer, Emily (International Food Policy Research Institute, 2019)
There is growing recognition of the importance of women’s empowerment in its own right and for a range of development outcomes, but less understanding of what empowerment means to rural women and men. The challenge of measuring empowerment, particularly across cultures and contexts, is also garnering attention. This paper synthesizes qualitative research conducted conjointly with quantitative surveys, working with eight agricultural development projects in eight countries, to develop a project-level Women’s Empowerment in Agriculture Index (pro-WEAI). The qualitative research sought to identify emic meanings of “empowerment,” validate the domains and indicators of the quantitative index, provide greater understanding of the context of each project and of strategies for facilitating empowerment, and test a methodology for integrating emic perspectives of empowerment with standardized etic measures that allow for comparability across contexts.